Entrepreneurial orientation and internationalisation scope: A study of Malaysian International SMEs - Tze Cheng Chew (Universal Publishers - Boca Raton, Florida, USA, 2022)
This study aims to enrich understanding of the effects of entrepreneurial orientation (EO) on the internationalisation of small and medium enterprises (SMEs) by considering the effects of individual EO dimensions that support firms to broaden their scope of internationalisation. Design/methodology/approach: A sample of 253 international SMEs is collected in Malaysia and explored using logistic regression analysis. The findings reveal the nuanced independent roles of two individual EO dimensions, i.e. innovativeness and pro-activeness, on the firm's tendency to enter multiple foreign countries. The study uses single respondent and cross-sectional data that might have some limitations in terms of data rigorousness and findings generalisability. The findings provide important managerial and policymaking implications. The findings advance international entrepreneurship (IE) research by enriching the understanding of internationalisation scope by explicating the individual EO dimensions effect on the likelihood of firms expanding to multiple foreign countries.